Pengaruh Teknologi Digital terhadap Peningkatan Pendapatan UMKM di Dusun Serut - Nugroho, Indra Ibnu (Economie: Jurnal Ilmu Ekonomi, 2024)
Efforts to accelerate the economic and economic turnover of a nation are one of the strategic procedures of public authorities in empowering society, one of which is through the presence of Miniature, Small and Medium Enterprises (MSMEs). Along with technological advances and developments, digital technology is currently rapidly influencing society in supporting business activities, both large and small, so that they can be recognized globally. The main aim of this research is to examine how the use of cutting-edge technology contributes to increasing the income of MSMEs in Serut area. The system used combines different repetitive inspection procedures with the help of the SPSS 16.0 variation program. The information used is important and additional information. Research information is collected. by the scientists themselves with a selection procedure as a perception by utilizing observation polls using a questionnaire list. The results of the research show that the use of digital technology has a positive and significant effect on increasing the income of Micro, Small and Medium Enterprises (MSMEs) in the Serut area. From this research the use of digital technology can increase the amount of production, increase income and increase the marketing area, while the obstacles that the problem faced is that technology mastery has not been maximized and there is no understanding of well-structured management.